The Genesis of Sri Lanka Malay : a Case of Extreme Language Contact. - Nordhoff, Sebastian (Brill's studies in South and Southwest Asian languages., 2012)
Sri Lanka Malay shows extreme language contact: Malay phonology and lexicon are squared with clearly Indian morphosyntax and semantics. Historical, anthropological, typological and structural approaches shed light on the complex genesis and rapid evolution of this language.